EFFICACY OF SELECTED PLANT EXTRACT AGAINST MAJOR INSECT PEST ON TWO (2) VARIETIES OF COWPEA (Vigna unguiculataea L. Walp) IN GUINEA SAVANNAH OF NIGERIA - Musa, M. A. (Nigerian Journal of Agriculture and Agricultural Technology, 2026)
The Field experiment was conducted at Prince Abubakar Audu University Student Demonstration and Research Farm (Lat 7 o61N and Long 7 o431E) in guinea savannah of Nigeria The main objective of the study is to investigate the efficacy of selected plant extract against major insect pest on two (2) varieties of cowpea (vigna unguiculataea l. walp) in guinea savannah of Nigeria. The experimental Design was laid in a Randomized Complete Block Design. The experiments were replicated four times making a total of 24 plots in all. Treatments consisted of (Fumpea I (V1) and Sampea, 20 (V2) and Control, Neem leaf extract, Cypermethrin and Jatropha leaf extract this gives 2 x 4 factional combinations of treatments. The parameters measured includes: plant height (cm) number of leaves, Leaf Area (cm2), Number of Pods/Plant, Number of Seeds/Plant, Pod Length (cm), and Grains Yield (kg/ha). Results showed insecticide treatments significantly affected only plant height (28.81 cm), leaf number (55.96), and grain yield (1820.69 kg/ha) at 6 weeks after sowing, with Neem extract yielding the highest values. Variety significantly influenced only leaf area at 2 weeks (Sampea-20: 15.72 cm²). No treatment significantly impacted leaf area (overall), pods/plant, seeds/plant, or pod length. Interactions between insecticides and varieties were not significant for any parameter. It was concluded that Neem leaf extract enhances key growth components and grain yield in cowpea. Sampea-20 is recommended alongside Neem extract for optimal cowpea production in the study area and similar ecologies.